2016
DOI: 10.18869/acadpub.aassjournal.4.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-actinin-3 R577X Polymorphism Profile of Turkish Professional Hip-Hop and Latin Dancers

Abstract: Actins are small globular filaments functioning in cell processes like muscle contraction, and stabilized to the sarcomeric Z-discs by actin binding proteins (actinins). One of the important gene coding for actin binding proteins in fast twitch fibers is alpha-actinin-3 (ACTN3). In this research, we have conducted a gene profile study investigating the genotype and allele distributions of ACTN3 R577X polymorphism in Turkish professional hip-hop and latin dancers and compared them to non-dancers as a control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Lastly, a study of self-reported injuries in hip-hop dancers that included 212 breakers in the cohort reported an average of 3.5 injuries per dancer per 6 months, with the most common injury sites being the foot-ankle, forearm-wrist, hand, hip, and knee. 15 Even though there has been a start in investigating breaking from physiological, 16,17 psychological, 18,19 and biomechanical 7,20 perspectives, epidemiological injury data are still sparse. 15 The aim of this study was to collect self-reported breaking-specific injury data using a 12-month recall methodology that also included information on participants' lifestyle and training experience.…”
Section: An Online Cross-sectional Cohort Study Of Breakersmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, a study of self-reported injuries in hip-hop dancers that included 212 breakers in the cohort reported an average of 3.5 injuries per dancer per 6 months, with the most common injury sites being the foot-ankle, forearm-wrist, hand, hip, and knee. 15 Even though there has been a start in investigating breaking from physiological, 16,17 psychological, 18,19 and biomechanical 7,20 perspectives, epidemiological injury data are still sparse. 15 The aim of this study was to collect self-reported breaking-specific injury data using a 12-month recall methodology that also included information on participants' lifestyle and training experience.…”
Section: An Online Cross-sectional Cohort Study Of Breakersmentioning
confidence: 99%
“…Even though there has been a start in investigating Breaking from a physiological 16,17 , psychological 18,19 and biomechanical 7,20 perspective, injury epidemiological data are still sparse 15 . The aim of this study was to collect self-report breaking-specific injury data using a 12-month recall methodology that also includes information on participants', lifestyles and training experiences.…”
mentioning
confidence: 99%
“…The number of participants was determined as 21 using the Minitab program in the determination of the sample size of the study (Figure A) based on Mutlucan et al (2017). The research participants involved 35 volunteering bodybuilding athletes who have been actively involved in sports for at least 10 years.…”
Section: Determining the Number Of Participantsmentioning
confidence: 99%
“…Angiotensin converting enzyme (ACE) insertion/ deletion and alpha-actinin-3 (ACTN3) R577X are the most widely analyzed polymorphisms in sports genomics (1,2). Besides these, other SNPs are still under investigation, which are considered to have an important effect on athletic performance.…”
Section: Dear Editormentioning
confidence: 99%